Dynamical system approach to solving linear programming problems and applications in economic modelling - Tverdokhlib, I.P.; Prykarpatsky, O.A. (Нелінійні коливання, 2002)
A class of dynamycal systems on symplectic manifolds solving linear programming problems is described. The structure of orbit space is analyzed in the framework of the Marsden – Weinstein reduction scheme. Some examples having applications in modern macro-economical modelling are treated in detail. Описано клас динамiчних систем на симплектичному многовидi, що розв’язують задачi лiнiйного програмування. Проведено аналiз простору орбiт з точки зору принципу редукцiї Марсдена i Вайнштейна. Детально розглянуто приклади застосувань у моделюваннi сучасних макроекономiчних процесiв.